Enhancing higher-order thinking skills among pre-service teachers in China: a framework of constructivist smart learning environments integrating cognitive and motivational factors - Ni, Nie; Roslan, Samsilah; Maarof, Aini Marina; Sulaiman, Tajularipin; He, Sun (Human Resources Management Academic Research Society (HRMARS), 2023)
Teaching Higher-Order Thinking Skills (HOTS) in Constructivist Smart Learning Environments (CSLE) has been treated as an essential goal of higher education in many countries. With new roles and functions in smart classrooms, learners' factors influencing teaching HOTS are very different from traditional classrooms. Although some cognitive and motivational factors always play an important role in teaching HOTS in CSLE, the lack of useful information and knowledge has caused many teachers to fail to teach HOTS effectively in smart classrooms in China. Based on previous research and related theories,this study aims to propose a framework of constructivist smart learning environments integrating cognitive and motivational factors for teaching higher-order thinking skills The results of this study were expected to contribute some effective guidance for teaching HOTS in constructivist smart learning environments among pre-service teachers in China.